Pengurusan Tarian Tradisional Igal-Igal Masyarakat Bajau, Sabah - Riana, Binti Mohd Jim . (Universiti Malaysia Sarawak (UNIMAS), 2017)
Studies conducted in respect of the Management of Traditional Dance of Bajau community which is known as ‘Igal-Igal Dance’ in Sabah. With the aim to identify ways of managing traditional dance performed by the Jabatan Kebudayaan dan Kesenian Negara (JKKN) Sabah and other several dance association in Semporna. In addition, to investigate the challenges faced by organization and association as well as the methods used in addressing the challenges and problem faced. By using multiple data collection methods such as observation, interviews and documentation, researchers have obtained the necessary data and information. This study clearly shows the dif erence about traditional dance management by JKKN Sabah organization and management by association of dance forms in Semporna. JKKN Sabah organization management run Igal-Igal dance more proactively and regularly, while the association of dance occurring in Semporna which is Arung Lingkatan Association, Waris Anak Selakan Association and Penggiat Seni Anak Semporna Association show the management is more concerned with the skills acquired by the manager of the association to ensure that the management activities of this traditional dances executable well. Therefore, it is concluded that an ef ective management is influenced by the used of adequate human resources, financial bases, strategic, and active and efective promotion.